Flail arm syndrome patients exhibit profound abnormalities in nerve conduction: an electromyography study - Sang, Qiuling; Wang, Sijian; Shi, Yaoxun; Chen, Jiajun (Somatosensory & motor research, 2019)
Flail arm syndrome (FAS) is a rare degenerative disease of the nervous system and a variant of amyotrophic lateral sclerosis (ALS). In the current study, we sought to further delineate electromyographic changes in sensory and motor conduction of the median nerve in four FAS patients and also described one representative case of FAS in a 63-year old Chinese male patient who was admitted because of aggravating limb myasthenia for three months. Electromyography showed that FAS patients exhibited variable electromyographic changes in sensory conduction of the median nerve. Abnormal conduction velocity of the sensory nerve in bilateral median nerves was observed in one patient but normal in two other patients. Two patients had a marked reduction in median sensory nerve action potential amplitude. In addition, one patient showed significant reduction in the conduction velocity and motor nerve action potential amplitude. The latency of motor conduction of bilateral median nerves was markedly prolonged. Furthermore, the incidence rate of the F wave in the right median nerve ranged from 5% to 100%. Furthermore, all four patients exhibited abnormalities in needle electromyography in at least three regions of the four regions examined with massive denervations in large and widened motor units and diminished recruitment of motor units, indicating the simultaneous presence of both acute denervation and chronic nerve regeneration. In conclusion, this is the first detailed study of electromyographic changes in FAS and the findings help improve clinicians' understanding of this disease and differentiating the diagnoses of FAS from ALS.